2002
DOI: 10.1046/j.1365-277x.2002.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into school children's knowledge and awareness of food and nutrition

Abstract: With the diet and exercise behaviours of UK school children showing little improvement over recent years, the need for dietary change is clearly indicated. This study aimed to assess the nutritional knowledge and understanding of primary school children in order to identify the most effective format for future nutrition messages. A qualitative methodology was employed and 114 children, aged 7-11 years, took part in 23 focus groups separated by age, gender and socio-economic status (SES). Issues discussed inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
4
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 32 publications
9
68
4
5
Order By: Relevance
“…It is also interesting to note that there were minimal gender differences and that girls, if anything, had slightly lower nutrition knowledge scores than boys. This is in contrast to previous literature, which found that girls achieved 85 % accuracy compared with only 65 % accuracy for boys in a sample of 7-11-year-old children (14) . Generalisability of the results may be limited by a selfselection bias because participants who volunteered for the study may have a greater interest in nutrition and may therefore place greater importance on teaching their children about healthy food than the general public.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also interesting to note that there were minimal gender differences and that girls, if anything, had slightly lower nutrition knowledge scores than boys. This is in contrast to previous literature, which found that girls achieved 85 % accuracy compared with only 65 % accuracy for boys in a sample of 7-11-year-old children (14) . Generalisability of the results may be limited by a selfselection bias because participants who volunteered for the study may have a greater interest in nutrition and may therefore place greater importance on teaching their children about healthy food than the general public.…”
Section: Discussioncontrasting
confidence: 99%
“…This level of knowledge is consistent with other well established studies. (Edwards & Hartwell, 2002;Fitzgerald, Heary, Nixon, & Kelly, 2010;Hart, Bishop, & Truby, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, children did demonstrate some level of discernment when it came to assessing the media as a source of nutrition information. For example, they were very distrustful of the Sunny Delight advertisements (a topical food advertisement at the time of data collection) and felt that they were misleading, a perception also noted by Hart et al (2002). Nutrition education has the potential to equip children with the skills they need to deal with the media pressures they will inevitably face throughout life, thereby helping them to become discerning consumers.…”
Section: Discussionmentioning
confidence: 99%